Văn học Việt Nam thế kỷ XX - Nguyễn, Cừ (Văn học, 2010)
Giới thiệu các tác phẩm thơ của nhiều tác giả: Khuyết Danh, Nguyễn Thế Long, Nguyễn Trọng Đông, Trần Lê Hương, Nguyễn Văn Đức, Phan Trọng Bình, Lê Thành Lập...